High School Dropout and the Intergenerational Transmission of Crime - Davide Dragone; Giuseppe Migali; Eugenio Zucchelli (Institute of Labor Economics (IZA), 2021)
We explore the relationship between high school dropout and pupils' adult crime by accounting for the role of the intergenerational transmission of crime. We employ a human capital model of schooling and crime and show that the intergenerational transmission of crime could have a direct effect on adult crime as well as an indirect effect mediated by high school dropout. We empirically assess the relevance of these relationships using fixed effects linear probability models and inverse probability weighting regression adjustment on US data from the National Longitudinal Study of Adolescent to Adult Health. We find that dropping out from high school and having a convicted father increase the probability of adult crime, with the former presenting a larger effect. Our empirical models also suggest that having a convicted father increases the probability of dropping out from school. This reveals that paternal crime imposes a double penalty on children: it increases their probability of committing crimes later on in life both directly and indirectly via school dropout. When considering the role of the environment, we find that while an early exposure to high levels of crime exacerbates dropping out, it has no direct long-term effect on adult crime. Finally, we show that individual traits may also play a role, as pupils with lower levels of cognitive skills present higher probabilities of adult criminal behaviour and stronger intergenerational effects.
Keywords: I26; J62; K42; 330; intergenerational transmission; crime; high school dropout; Add Health